2011
DOI: 10.1590/s0482-50042011000200002
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidades em pacientes com osteoartrite: frequência e impacto na dor e na função física

Abstract: Introduction: As the prevalence of osteoarthritis (OA) increases with age, the coexistence of other chronic diseases is common. Objectives: To evaluate the frequency of comorbidities in OA patients and to measure their impact on pain and physical function of those patients. Methods: Cross-sectional study in OA patients of a public rheumatology clinic. Pain was measured by use of the Visual Analogue Scale (VAS) and physical function by use of the Lequesne's and SACRAH indices. A screening for depression was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 27 publications
0
5
1
8
Order By: Relevance
“…Researchers report that such association is probably due to the fact that women have a longer life expectancy and, consequently, a bigger risk of developing incapacitating chronic diseases. 19,24,25 Although data from the present study showed the prevalence of female among the elderly with depression, a statistically insignificant association was found between the gender variable and the GDS-15 instrument, as opposed to the literature consulted.…”
Section: Resultscontrasting
confidence: 91%
See 1 more Smart Citation
“…Researchers report that such association is probably due to the fact that women have a longer life expectancy and, consequently, a bigger risk of developing incapacitating chronic diseases. 19,24,25 Although data from the present study showed the prevalence of female among the elderly with depression, a statistically insignificant association was found between the gender variable and the GDS-15 instrument, as opposed to the literature consulted.…”
Section: Resultscontrasting
confidence: 91%
“…It should be pointed out that such pathologies are related to chronic pain and, consequently, to the association between this clinical finding, depressive symptoms, and sleep disorders, which alternate as an uninterrupted cycle. 19 So, depression emerges in postmodern society as evidence of man's vulnerability to new rhythms, values, and contexts, materializing latent expiatory suffering through cessation of interest in the modern world, in a mixture of progressive loss of identity by recriminations against themselves and decline in self-esteem. 17,18 This scenario interferes negatively in personal and social productivity, enabling disabilities across the age range, races, faith, gender, socioeconomic status, as well as historical, cultural and geographical boundaries between nations.…”
Section: Resultsmentioning
confidence: 99%
“…In studies showing that improvement, all participants received physical therapeutic care after surgery until total rehabilitation. 43,44 Other authors, however, have found a correlation between the presence of pain, depression, OA, and alteration in functionality. 45 Several patients can have problems, such as muscle weakness and contracture, reduced range of motion, diffi culty in walking, and limitation of daily life activities, despite replacing the injured joint with a prosthesis.…”
Section: Discussionmentioning
confidence: 98%
“…A idade foi uma variável que mostrou associação estatisticamente significante em relação à presença de OA (p=0,01), com maiores idades entre os pacientes do grupo 1, esse dado corrobora com os resultados de pesquisas na mesma temática (CHACUR et al, 2010;LEITE et al, 2011). O aumento da idade aumenta à incidência de OA em todas as articulações.…”
Section: Discussionunclassified